THE ROLE OF RESOURCE PLANNING (ERP) SYSTEMS IN RAISING THE LEVEL OF QUALITY PERFORMANCE FOR PROJECT MANAGEMENT - Mohammed Sadeq Mohammedali; Taicir Moalla Loukil (American Journals, 2024)
The large size of projects in Iraq requires the provision of material, a human, administrative, financial and engineering resource, which requires searching for the most important modern means and systems and programming them to ensure the implementation and completion of projects within a high level of performance quality and within the axes of time, cost and quality specified for them. This research dealt with the concept of inbound planning systems (ERP). Which enhances the effectiveness of the performance quality activity, which in turn has a positive impact on the level of project management performance, by clarifying the role of resource planning systems (ERP) in raising the level of performance quality for project management, through an applied field study on projects in the Iraqi governorates of Baghdad and Karbala, where a sample was formed. The study included project managers who numbered (218) people working in government institutions such as the Projects Department affiliated with each governorate, the Projects Department affiliated with the Baghdad Municipality, the Planning and Follow-up Directorate, and the Engineering Planning Department affiliated with Karbala Governorate. The researcher used the descriptive analytical approach and the questionnaire as a tool for the study, as this research aims to clarify The positives of the concept of inbound planning systems (ERP) and the basic dimensions that depend on it, which are human resources, production, customer relationship management, supply chain management, resource engineering and operations, after formulating the research problem that was built through problems faced by project managers, specialists, relationship and officials through the disruption of the work of government projects. On the basis of it, the study hypotheses were formulated, and the study objective was set.The study reached many results through the second questionnaire to determine the extent of the relationship between inbound planning systems (ERP) and improving the quality of performance for project management through analyzing them with the SPSS program, the most important of which were: the interconnection and the important impact of inbound planning systems (ERP) on the quality level. Performance for project management. The research also included many recommendations, the most important of which was the necessity of activating the concept of introducing modern and globally developed systems in project management, especially those that have been used by successful projects, and the necessity of adopting the dimensions of resource planning systems (ERP) in the institutions concerned with project implementation in all state institutions. Because it leads to raising the level of quality of project management performance, which in turn leads to the success of projects to very high levels, and taking adequate preventive measures to prevent the occurrence of problems that affect the level of project management performance through coordination and continuous exchange of information between senior management and its executive cadres, and developing the scientific and administrative knowledge of Project managers, especially in the departments and divisions responsible for designing, planning and following up on the implementation of projects and setting clear schedules and specifications about the quality of performance for all administrative levels, by subjecting them to specialized courses and seminars and granting them a certificate of experience in these fields to benefit from this experience in institutions, government departments or private companies.
Keywords: Resource planning systems; Quality performance of Project Management; Supply chain management; Customer Relationship Management; Planning; Resource and Process Engineering; Feasibility study; Implementation; Quality.